Whether it is economical to use combined heat and power (CHP) system for the efficient utilization of associated petroleum gas in oil extraction sites in China: A cost-benefit analysis considering environmental benefits - Chen, Mingjian (Frontiers in Environmental Science, 2022)
The efficient use of associated petroleum gas with combined heat and power (CHP) systems in oil extraction sites has proven to be technically feasible, but its economic inefficiency continues to deter oil companies from using CHP, given that simple fuel cost reductions do not yield significant positive returns in the face of large investments in purchasing and maintaining CHP. This research constructs a cost-benefit analysis model, which includes the monetized environmental benefits generated by CHP. A pilot experiment operated in a certain oilfield in Shandong province shows that the annual difference between the reduction in fuel costs and the investment in purchase and maintenance of CHP is only about ¥210,000 per device. However, when environmental benefits including health benefit and low-carbon benefit are included in the model, the annual environmental benefits of a single equipment update can be about ¥760,000, and the overall annual net benefits will reach about ¥970,000. It is concluded that the application of CHP in oil extraction sites is economically efficient, taking into account the environmental benefit it can produce. The research results will help oil companies use CHP to make more contributions to carbon and air pollutant emission reduction. However, considering that a large number of CHP systems can form a distributed energy structure, the proposed model still has limitations.